1978
DOI: 10.2307/1936571
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Retention by the Root Mat of an Amazonian Rain Forest

Abstract: Surface root mats on oxisols and spodosols near San Carlos de Rio Negro, Venezuela, were sprayed with (45)Ca and (32)P to simulate the addition of nutrients to the soil surface through leaching of decomposing litter, and through precipitation and throughfall. Collections from lysimeters placed below the root mat and humus layer showed that in all but 1 case, <0.1% of the radiotracers leached past the root–organic mat, and leaching stopped completely after 1 to 2 months. Through analysis of root mat samples, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
14

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(131 citation statements)
references
References 5 publications
1
116
0
14
Order By: Relevance
“…Most of the demand for P in natural forests can be met by rapid cycling of P in organic matter (Attiwill and Adams 1993;Turner and Engelbrecht 2011) and fine roots growing into the organic horizons acquire P directly from decomposing litter as it is mineralized (Herrera and others 1978;Stark and Jordan 1978;Tobon and others 2004), bypassing the mineral soil (Witkamp 1971). The increase in P uptake despite the lack of change in soil extractable P pools in the double-litter plots suggests that most of the plant demands for P were met by direct cycling from the forest floor.…”
Section: Phosphorusmentioning
confidence: 99%
“…Most of the demand for P in natural forests can be met by rapid cycling of P in organic matter (Attiwill and Adams 1993;Turner and Engelbrecht 2011) and fine roots growing into the organic horizons acquire P directly from decomposing litter as it is mineralized (Herrera and others 1978;Stark and Jordan 1978;Tobon and others 2004), bypassing the mineral soil (Witkamp 1971). The increase in P uptake despite the lack of change in soil extractable P pools in the double-litter plots suggests that most of the plant demands for P were met by direct cycling from the forest floor.…”
Section: Phosphorusmentioning
confidence: 99%
“…Furthermore, fine root development in the topsoil, especially in oligotrophic forests is often considered as a nutrient conservation mechanism (Jordan 1991). Stark & Jordan (1978) have shown that fine roots are constitute an efficient nutrient trap, capable of recovering more than 99% of P and Ca, spread in the topsoil.…”
Section: Influence Of Soil Depth On the Vertical Distribution Of Finementioning
confidence: 99%
“…-O maior estoque de nutrientes nas florestas tropicais está na parte aérea das árvores, o que não ocorre com outro tipo de cobertura vegetal, como pastagem, em que a maior parte dos nutrientes se encontra no solo (Fonseca et al, 1993); -Presença de muitas raízes finas na superfície do solo penetrando a manta, freqüentemente observadas em florestas tropicais (Stark & Jordan, 1978;Nunes, 1980), o que pode explicar, em parte, como se dá a manutenção de uma floresta natural não perturbada sobre um solo de baixa fertilidade; -Equilíbrio entre demanda e liberação de nutrientes, favorecido pela diversidade de espécies (Drumond et al, 1997); -Ciclagem interna, principalmente do P e do N (Reis & Barros, 1990); -Solos de florestas tropicais úmidas sob elevadas temperaturas e pluviosidades sofrem um intemperismo intenso; assim, neste processo há grande lixiviação de elementos, com perda de Na, K, Ca, Mg e Si, além de favorecer a formação de argilominerais com baixa capacidade de reter cátions, enriquecendo os solos de óxidos de Fe e Al, que têm grande capacidade de fixar P (Clevelário Junior, 1996 Juntamente com as Matas de São João da Várzea, Jardim Botânico e Jangadinha, forma uma área verde amenizadora da ação poluente do Distrito Industrial do Curado, na Bacia Hidrográfica do Rio Tejipió e atua, também, como refúgio da fauna e flora (FIDEM, 1982;FIDEM, 1993).…”
Section: Introductionunclassified